Non-melanoma skin cancer treated with high-dose-rate brachytherapy and Valencia applicator in elderly patients: a retrospective case series - Delishaj, Durim; Laliscia, Concetta; Manfredi, Bruno; Ursino, Stefano; Pasqualetti, Francesco; Lombardo, Ezio; Perrone, Franco; Morganti, Riccardo; Paiar, Fabiola; Fabrini, Maria Grazia (Journal of Contemporary Brachytherapy, 2015)
Purpose The incidence of non-melanoma skin cancer (NMSC) has been increasing over the past 30 years. Basal cell carcinoma and squamous cell carcinoma are the two most common subtypes of NMSC. The aim of this study was to estimate tumour control, toxicity, and aesthetic events in elderly patients treated with high-dose-rate (HDR) brachytherapy (BT) using Valencia applicator. Material and methods : From January 2012 to May 2015, 57 lesions in 39 elderly eligible patients were enrolled. All the lesions had a diameter ≤ 25 mm (median: 12.5 mm) and a depth ≤ 4 mm. The appropriate Valencia applicator, 2 or 3 cm in diameter was used. The prescribed dose was 40 Gy in 8 fractions (5 Gy/fraction) in 48 lesions (group A), and 50 Gy in 10 fractions (5 Gy/fraction) in 9 lesions (group B), delivered 2/3 times a week. The biological effective dose (BED) was 60 Gy and 75 Gy, respectively. Results : After median follow-up of 12 months, 96.25% lesions showed a complete response and only two cases presented partial remission. Radiation Therapy Oncology Group – European Organization for Research and Treatment of Cancer (RTOG/EORTC) G 1-2 acute toxicities were observed in 63.2% of the lesions: 56.3% in group A and 77.7% in group B. Late G1-G2 toxicities was observed in 19.3% of the lesions: 18.8% in group A and 22.2% in group B, respectively. No G3 or higher acute or late toxicities occurred. In 86% of the lesions, an excellent cosmetic result was observed (87.5% in group A and 77.8% in group B). Six lesions had a good cosmetic outcome and only 2.3% presented a fair cosmetic impact. Conclusions : The treatment of NMSC with HDR-BT using Valencia surface applicator is effective with excellent and good cosmetics results in elderly patients. The hypofractionated course appears effective and no statistical differences were observed between the two groups analysed.